2008
DOI: 10.1073/pnas.0805903105
|View full text |Cite
|
Sign up to set email alerts
|

Striatum and pre-SMA facilitate decision-making under time pressure

Abstract: Human decision-making almost always takes place under time pressure. When people are engaged in activities such as shopping, driving, or playing chess, they have to continually balance the demands for fast decisions against the demands for accurate decisions. In the cognitive sciences, this balance is thought to be modulated by a response threshold, the neural substrate of which is currently subject to speculation. In a speed decision-making experiment, we presented participants with cues that indicated differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

83
810
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 604 publications
(900 citation statements)
references
References 32 publications
83
810
7
Order By: Relevance
“…This shift to striatum-mediated learning has also been found when participants performed the weather prediction task under cognitive load (Foerde et al, 2006). In studies of the speed-accuracy tradeoff, increased activation was found in the striatum during trials with speed emphasis compared to trials with accuracy emphasis (Forstmann et al, 2008;van Veen et al, 2008), suggesting that enhanced striatal activity may be critical in reducing inhibitory control and facilitating speeded responses (Bogacz et al, 2010). Here, we significantly expand these findings by directly demonstrating that increased time pressure decreases the involvement of frontal and parietal regions and shifts probabilistic multi-cue decision-making to the striatum, even after the completion of initial cue learning.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This shift to striatum-mediated learning has also been found when participants performed the weather prediction task under cognitive load (Foerde et al, 2006). In studies of the speed-accuracy tradeoff, increased activation was found in the striatum during trials with speed emphasis compared to trials with accuracy emphasis (Forstmann et al, 2008;van Veen et al, 2008), suggesting that enhanced striatal activity may be critical in reducing inhibitory control and facilitating speeded responses (Bogacz et al, 2010). Here, we significantly expand these findings by directly demonstrating that increased time pressure decreases the involvement of frontal and parietal regions and shifts probabilistic multi-cue decision-making to the striatum, even after the completion of initial cue learning.…”
Section: Discussionmentioning
confidence: 59%
“…Specifically, learning the weather prediction task under stress induced by the cold pressor test has been associated with increased use of implicit, striatum-mediated strategies (Schwabe and Wolf, 2012). Similarly, time pressure on perceptual decision-making has been associated with a deterioration in information processing in early sensory areas (Ho et al, 2012) and increased activity in the striatum (Bogacz et al, 2010;Forstmann et al, 2008), indicating that the striatum may promote faster but possibly premature or sub-optimal decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The connectivity of this region to motor regions is abnormal in PD38 and modulated by dopamine 39. Furthermore, preSMA is involved in decreasing motor threshold during the speed–accuracy tradeoff 40. The observed overactivity of preSMA might therefore constitute an aberrant striatal feedback signal that causes an abnormal induction of internally generated movements and hereby contributes to the emergence of dyskinesias.…”
Section: Discussionmentioning
confidence: 99%
“…This speed-accuracy tradeoff can be straightforwardly implemented in sequential sampling models, which not only account for performance in a wide range of perceptual tasks (Brown & Heathcote, 2005;Ratcliff & McKoon, 2008) but can also be plausibly linked to neurophysiological correlates of decision making (Bogacz, Wagenmakers, Forstmann, & Nieuwenhuis, 2010;Forstmann et al, 2008Forstmann et al, , 2010Forstmann et al, , 2011Ho et al, 2012;Ivanoff, Branning, & Marois, 2008;Philiastides, Ratcliff, & Sajda, 2006;van Veen, Krug, & Carter, 2008). In general, decision making in sequential sampling models is based on the accumulation of evidence over time until a boundary (or criterion) is reached and an associated response is initiated (Brown & Heathcote, 2005Busemeyer & Townsend, 1993;Diederich & Busemeyer, 2006;Hübner, Steinhauser, & Lehle, 2010;Ratcliff & Smith, 2004;Ratcliff, 1978;Usher & McClelland, 2001;White, Ratcliff, & Starns, 2011).…”
Section: Introductionmentioning
confidence: 99%